1998
DOI: 10.3109/08880019809167231
|View full text |Cite
|
Sign up to set email alerts
|

Infections Occurring During the Courses of Anticancer Chemotherapy in Children with All: A Retrospective Analysis of 59 Patients

Abstract: In a retrospective analysis we evaluated the occurrence of infections in 59 children with acute lymphoblastic leukemia (ALL) during the entire duration of their anticancer chemotherapy. We recorded a total of 245 infection episodes, 118 (50%) being during neutropenia and 119 (50%) during nonneutropenia. The infections most commonly detected during neutropenia were fevers of undetermined origin (36%), clinically or microbiologically defined focal infections (33%), and bacteremias (28%). During nonneutropenia, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 16 publications
1
41
1
Order By: Relevance
“…Thus, the true incidence of otitis, gastroenteritis, eye infections, or central nervous system (CNS) infections has not been well documented [21]. The aim of the present study is to assess the type, frequency, and severity of all types of infectious complications in a pediatric patient cohort with newly diagnosed ALL.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, the true incidence of otitis, gastroenteritis, eye infections, or central nervous system (CNS) infections has not been well documented [21]. The aim of the present study is to assess the type, frequency, and severity of all types of infectious complications in a pediatric patient cohort with newly diagnosed ALL.…”
Section: Introductionmentioning
confidence: 98%
“…The current cure rate of childhood ALL is more than 80% [13,18,19]. tract infection, and pneumonia are the most frequent infectious complications in febrile patients with ALL [8,21]. The widespread use of indwelling vascular catheters has altered the type of bacteremia seen overtime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 These infectious complications often lead to hospitalization and can be clinically significant, such as with bacteremia or fungemia. 4,5 Past studies have shown a marked immunosuppression, particularly a significant reduction in B lymphocytes, [6][7][8][9][10][11][12][13] and associated hypogammaglobulinemia, during the maintenance phase of chemotherapy for childhood ALL. Intravenous immunoglobulin (IVIG) has been used in a variety of clinical settings to reduce the frequency and severity of bacterial infections in pediatric and adult patients with primary and secondary antibody deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Infections increase the risk of death and may also increase the risk of relapse due to interruption of treatment and need for a decrease in the dose of chemotherapeutic agent. 17 Nosocomial infections are important clinical complication as it can cause considerable morbidity and mortality; thus increase hospital stay and healthcare cost. Monitoring nosocomial infection rate is of great importance to establish preventing measures.…”
mentioning
confidence: 99%